2020
DOI: 10.1111/ejn.14668
|View full text |Cite
|
Sign up to set email alerts
|

Do tone duration changes that elicit the mismatch negativity also affect the preceding middle latency responses?

Abstract: The human brain can automatically detect sound changes. Previous studies have reported that rare sounds presented within a sequence of repetitive sounds elicit the mismatch negativity (MMN) in the absence of attention in the latency range of 100–250 ms. On the other hand, a previous study discovered that occasional changes in sound location enhance the middle latency response (MLR) elicited in the latency range of 10–50 ms. Several studies have reported an increase in the amplitude of the MLR within the frame … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Several neuroimaging studies have revealed that deviations in the spatial location of stationary sound sources generated MMN responses, and the stimulus-speci c adaptation (SSA) versus MMN generation potentially being able to clarify the issues of horizontal localization [7][8][9] . Auditory MMN is a widely used ERP component that re ects pre-attentive auditory processing at a latency of about 100-250ms 10 . The neural discriminative response, which is re ected by the MMN, has been used as a tool to study a variety of cognitive disorders in audition.…”
Section: Introductionmentioning
confidence: 99%
“…Several neuroimaging studies have revealed that deviations in the spatial location of stationary sound sources generated MMN responses, and the stimulus-speci c adaptation (SSA) versus MMN generation potentially being able to clarify the issues of horizontal localization [7][8][9] . Auditory MMN is a widely used ERP component that re ects pre-attentive auditory processing at a latency of about 100-250ms 10 . The neural discriminative response, which is re ected by the MMN, has been used as a tool to study a variety of cognitive disorders in audition.…”
Section: Introductionmentioning
confidence: 99%